Petrographic and Geochemical Analyses of Kirana Hills Shield Rocks around Sargodha and Economic Potential : Petrographic and Geochemical Analyses of Kirana Hills Shield Rocks around Sargodha and Economic Potential - Muhammad Waseem Khan; Syed Abbas Sultan; Iftikhar Alam; Muhammad Saqib Izhar (International Journal of Economic and Environmental Geology, 2017)
The present study deals with geochemical and petrographic analysis of the Kirana Hill shield rocks of Punjab plains from Buland, Hachi, Shaheen Abad, Shaikh and Machh hills. On basis of the current studies certain modifications have been made in the classification and nomenclature of rocks exposed in the study areas. Chemical analyses have also been carried out in order to calculate Cross Iddings, Pirsson, and Washington (CIPW) norms”, to strengthen nomenclature scheme and finally rocks are classified by using “MAGMA SOFTWARE”. Rhyolites predominate over the basalts/dolerites, andesites, and phyllite/ slate. Rhyolitic rocks are light grey, greenish grey and light brown in color, aphanitic in nature. The observed microscopic textures are aphyric, phyric or porphyritic and micropoikilitc. Moreover, some rhyolitic rocks also show flow texture. They are either cryptocrystalline to microcrystalline or microcrystalline to cryptocrystalline. No glassy material has been observed in any thin section. Mafic rocks are characterized by the presence of ferromagnesian minerals with plagioclase. Andesites exhibit mainly porphyritic texture, but aphyric texture has also been observed in few samples. Hydrothermal alterations are also very common in these rocks. Other rock assemblages identified during laboratory studies from Kirana area include: tuffs i.e. (Lithic Crystal Tuff and Lithic Tuff), basaltic andesite, rhyodacite/ dacite, slate/ phyllite, ankeritic rocks/ veins and quartzofeldspathic veins. Our studies also reveal that no evidence of quartzite has been found in the samples collected from above mentioned areas of Kirana, although it has been reported in previous literature. Iron (Fe) has been observed in rhyolite as well as other volcanic rocks of Kirana hills, its presence suggests magma from deep mantle instead of crustal melting / anatexis. In the present analysis some primary and secondary copper minerals including chalcopyrite, atacamite and malachite have been identified. Some anomalous values of the Rare Earth Elements are also observed. Inclusive geological investigations are recommended for better studies to appraise the potential of Iron (Fe), Copper (Cu) and trace/Rare Earth Elements (REE) in the area. Keywords: Mineral, petrographic, chemical analyses, rhyolite, hydrothermal alterations, Kirana Hills.